The Colombian Roundtable for Sustainable Beef and Dairy: 2020 activities - Burkart, Stefan; Urrea Benítez, José Luis (Bioversity International and the International Center for Tropical Agriculture, 2020)
Despite the restrictions resulting from the COVID-19 pandemic, CIAT extended its strong involvement in the Colombian Roundtable for Sustainable Cattle Production (Mesa de Ganadería Sostenible, MGS) during 2020 – although in a different, virtual format. Apart from joining the regular meetings, CIAT co-organized a virtual 5-month seminar series on sustainable cattle production, which attracted several thousand participants from all over the globe. A national level policy for sustainable cattle production in Colombia was submitted to the Colombian Ministry of Agriculture for evaluation and, as a result of the pandemic, is still under review. We are confident that the policy will be released during 2021. In addition to the involvement in the Colombian Roundtable for Sustainable Cattle Production, CIAT became one of the leading institutions for the Colombian cero-deforestation agreements, in particular for the dairy and beef value chains.